Exploiting genetic polymorphisms in metabolic enzymes for rapid screening of Leishmania infantum genotypes - Marcello Ceccarelli; Aurora Diotallevi; Francesca Andreoni; Fabrizio Vitale; Luca Galluzzi; Mauro Magnani (Parasites & Vectors, 2018)
Abstract Background Leishmania infantum is the aetiological agent of visceral leishmaniasis (VL) and cutaneous leishmaniasis (CL). Numerous strains and/or zymodemes have been identified and characterized by multilocus enzyme electrophoresis (MLEE). MLEE is considered the reference method for L. infantum parasite typing and it is based upon enzyme electrophoretic mobility analysis from promastigote cultures. However, the MLEE technique is cumbersome, time-consuming and does not detect silent genetic mutations or nucleotide changes that give rise to amino acid changes that do not alter electrophoretic mobility. As a result of these difficulties, many DNA-based typing methods have been developed over the past few years. However, relative to the enzymes utilized in MLEE analysis, we observed a shortage of DNA sequences available in the GenBank database or an absolute lack of sequences belonging to specific zymodemes. The aims of the present study were to (i) implement the number of sequences coding for metabolic enzymes used in MLEE; (ii) identify polymorphisms that characterize L. infantum zymodemes most prevalent in the Mediterranean basin; and (iii) exploit these polymorphisms to develop a rapid screening test that would give results comparable with existing MLEE typing. Results Partial sequences of seven metabolic enzyme genes (malic enzyme, 6-phosphogluconate dehydrogenase, mitochondrial isocitrate dehydrogenase, glucose-6-phosphate isomerase, glucose-6-phosphate dehydrogenase, phosphoglucomutase and mannose phosphate isomerase) were obtained from 11 L. infantum strains. The comparison of these sequences with those obtained from GenBank allowed for the identification of a few polymorphisms that could distinguish several zymodemes. In particular, the polymorphism 390T>G in the malic enzyme gene has been exploited to develop a high-resolution melt (HRM)-based assay to rapidly differentiate the genotype 390T, associated with zymodemes MON-1, MON-72 and MON-201, evidencing a partial agreement between genotyping results and MLEE. The assay has been successfully applied to L. infantum clinical isolates and clinical samples. Conclusions A HRM-based assay for rapid identification of genotypes associated with the most common L. infantum zymodemes in the Mediterranean basin has been developed and its potential application in epidemiological research for L. infantum population screening, without parasite isolation and culturing, has been demonstrated.